2019
DOI: 10.3390/ijms20133323
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Deficiency Following Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is fairly common and annually affects millions of people worldwide. Post traumatic hypopituitarism (PTHP) has been increasingly recognized as an important and prevalent clinical entity. Growth hormone deficiency (GHD) is the most common pituitary hormone deficit in long-term survivors of TBI. The pathophysiology of GHD post TBI is thought to be multifactorial including primary and secondary mechanisms. An interplay of ischemia, cytotoxicity, and inflammation post TBI have been sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 111 publications
(150 reference statements)
0
24
0
3
Order By: Relevance
“…The most frequent causes of traumatic brain injury (TBI) are road accidents (the main cause, which represents 50% of all cases) followed by falls, accidents related to violence, head injury linked to sport (hockey, football, soccer), combat sports (boxing and kickboxing) characterized by chronic repetitive head injuries and accidental war trauma, including explosion lesions [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Posttraumatic hypopituitarism is generally characterized by an isolated anterior pituitary hormone Immunofluorescence in cryostat sections of young baboon anterior pituitary gland tested against the serum of a patient with isolated growth hormone deficiency GHD, in a primary step adding FITC goat sera anti-human immunoglobulins (left panel: (a) = simple immunofluorescence) and in a second immunostaining step adding rabbit antisera anti-GH followed by rhodamine goat sera anti rabbit IgG (right panel: (b) = double four-layer immunofluorescence).…”
Section: Autoimmunity and Growth Hormone Deficiency (Ghd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent causes of traumatic brain injury (TBI) are road accidents (the main cause, which represents 50% of all cases) followed by falls, accidents related to violence, head injury linked to sport (hockey, football, soccer), combat sports (boxing and kickboxing) characterized by chronic repetitive head injuries and accidental war trauma, including explosion lesions [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Posttraumatic hypopituitarism is generally characterized by an isolated anterior pituitary hormone Immunofluorescence in cryostat sections of young baboon anterior pituitary gland tested against the serum of a patient with isolated growth hormone deficiency GHD, in a primary step adding FITC goat sera anti-human immunoglobulins (left panel: (a) = simple immunofluorescence) and in a second immunostaining step adding rabbit antisera anti-GH followed by rhodamine goat sera anti rabbit IgG (right panel: (b) = double four-layer immunofluorescence).…”
Section: Autoimmunity and Growth Hormone Deficiency (Ghd)mentioning
confidence: 99%
“…Post-traumatic hypopituitarism is generally characterized by an isolated anterior pituitary hormone deficiency rather than multiple hormone deficiencies. Impairment of GH secretion and consequently of IGF-1 concentrations seems to be the most common early disorder after traumatic brain injury, both in the acute and chronic phase [25,29]. Concerning this, it has been suggested that impairment of GH and gonadotropin secretions is the most commonly pituitary disorder occurring post-TBI due to the more lateral location of somatotrophs and gonadotrophs at a pituitary level [25,26].…”
Section: Autoimmunity and Growth Hormone Deficiency (Ghd)mentioning
confidence: 99%
“…Patients with post-TBI GHD have a higher risk to achieve poor cognition outcomes than those with an intact somatotropic axis after trauma ( 87 ). Park et al showed that patients with GHD after TBI have decreased cerebral glucose metabolism in specific cortical areas involved in intellectual function, executive function, and working memory ( 88 ).…”
Section: Tbi-related Hypopituitarism: Clinical Presentationmentioning
confidence: 99%
“…PTHP, and in particular GHD, are often underdiagnosed: patients with post-TBI GHD seem to be diagnosed on average two and a half years later after the primary onset of disease when compared to those with Non-Functioning Pituitary Adenoma (NFPA) ( 87 ).…”
Section: Tbi-related Hypopituitarism: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation